2023
DOI: 10.1186/s12916-023-02821-x
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to inTerrupt RAbies Transmission for the Elimination Goal by 2030 In China (STRATEGIC): a modelling study

Abstract: Background A global plan has been set to end human deaths from dog-mediated rabies by 2030 ("Zero-by-30"), but whether it could be achieved in some countries, such as China, remains unclear. Although elimination strategies through post-exposure prophylaxis (PEP) use, dog vaccination, and patient risk assessments with integrated bite case management (IBCM) were proposed to be cost-effective, evidence is still lacking in China. We aim to evaluate the future burdens of dog-mediated human rabies de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Each has its uses and limitations. Models which incorporate spatio-temporal features [ 159 ] and climatic influences [ 112 ] allow more targeted evaluation of the effects of diseases in specific locations, and models can be used to design national control policies linked to surveillance [ 160 ]. Models that incorporate AI components are increasingly being used, for example in dengue prediction [ [161] , [162] , [163] ].…”
Section: Synthesis Toolsmentioning
confidence: 99%
“…Each has its uses and limitations. Models which incorporate spatio-temporal features [ 159 ] and climatic influences [ 112 ] allow more targeted evaluation of the effects of diseases in specific locations, and models can be used to design national control policies linked to surveillance [ 160 ]. Models that incorporate AI components are increasingly being used, for example in dengue prediction [ [161] , [162] , [163] ].…”
Section: Synthesis Toolsmentioning
confidence: 99%
“…In China, dog-mediated rabies accounts for 95% of rabies cases nationwide, with the rest being mediated by cats and wildlife [ 6 ]. Although studies have demonstrated that mass vaccination of dogs against rabies is the most cost-effective option for rabies eradication [ 7 ], the current level of canine rabies vaccination in China is still low [ 8 ], especially in the less economically developed rural areas of China, and falls far short of the 70% mark [ 9 , 10 ], so timely post-exposure prophylaxis (PEP) and post-exposure vaccination (PEV) for rabies-exposed patients remain important tools for rabies prevention and have important public health implications.…”
Section: Introductionmentioning
confidence: 99%